Lingual schwannoma in pediatric patients. - Manna, Francesco; Barbi, Egidio; Murru, Flora; Bussani, Rossana (J Craniofac Surg, 2012)
We present the case of a 15-year-old boy who presented to our emergency department because of a soft lesion growing on the back of his tongue. On examination, a vegetant mass on the posteromidline lingual part of the body of the tongue was noticed: it was not painful, even if the boy reported discomfort because of its size; there was no bleeding or signs of infection. The magnetic resonance imaging showed the lesion as trilobated and capsulated, but was not diriment to define a diagnosis; excisional biopsy was performed under general anesthesia, and the mass was identified as a schwannoma. Schwannoma, or neurilemmoma, is a benign tumor originating from Schwann cells of the nerve sheath surrounding peripheral nerves. It is slow-growing, usually solitary, and encapsulated. Intraoral schwannomas are rare and account for 1% of lesions of the head and neck region. There is no sex predilection. The symptoms depend on size and location of the tumor. Recurrence is rare after complete surgical resection. The present study aimed to retrospectively describe our experience with a case of neurilemmoma of the tongue presenting in childhood, the diagnostic methods used, the surgical decision, and the treatment outcome and to analyze the data and review the literature available on this type of tumor. The etiology, clinical presentation, differential diagnosis, and management are discussed.
Keywords: Adolescent; Diagnosis, Differential; Humans; Magnetic Resonance Imaging; Male; Neurilemmoma; Tongue Neoplasms